La reeducación postural y la actividad física en niños de diez años de la escuela de educación general básica Zoila Alvarado de Jaramillo - Romero Peña, Tatiana Cecibel (2016)
This research aims to investigate about Postural Reeducation and Physical Activity in Children Ten years of the School of General Education Basic Zoila Alvarado of Loja Jaramillo. Bad posture habits acquired at school as sitting in an awkward position, carry the backpack with excessive weight, standing in an inappropriate manner have allowed to determine whether physical activity influences the Postural Reeducation in children ten years of the School of Education level General Basic Zoila Alvarado Jaramillo. Postural reeducation is an innovative therapeutic and preventive method that treats muscle injuries, joint dysfunction, postural changes and corrects distortions has been created in order to correct different problems caused by poor posture taken by the body or diseases that have been acquired over the years it is more common in children of school age, which is why it is believed desirable physical activity especially to improve poor posture acquired by children in growth stage in addition to practicing physical exercises that will significantly improve health boy ; the type of research is qualitative, its kind of descriptive longitudinal study and its design is pre-experimental methods used are: deductive-inductive, historical and logical, analytical and descriptive statistical methods to measure knowledge to children through surveys, direct observation, postural assessment test that allowed the collection of dates. Los results demonstrate the lack of awareness in children about postural reeducation through physical exercises that improve bad posture, strain and even pain in the back, implement the proposed exercise we can show positive results. In conclusion, we can mention that the lack of knowledge about postural defects that cause bad body position can cause serious diseases such as scoliosis, lordosis and kyphosis. That is why training for children and teachers on this important issue in the health of schoolchildren is recommended.